2020
DOI: 10.1111/eip.12878
|View full text |Cite
|
Sign up to set email alerts
|

Global research priorities for youth mental health

Abstract: Aim: Over the past two decades, the youth mental health field has expanded and advanced considerably. Yet, mental disorders continue to disproportionately affect adolescents and young adults. Their prevalence and associated morbidity and mortality in young people have not substantially reduced, with high levels of unmet need and poor access to evidence-based treatments even in high-income countries. Despite the potential return on investment, youth mental disorders receive insufficient funding. Motivated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 81 publications
1
55
0
Order By: Relevance
“…There is general agreement on the importance of identifying youth mental health needs to improve preventive strategies and early intervention [2]. Despite the progress achieved over the past two decades, the number of studies conducted in the Arab world is scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is general agreement on the importance of identifying youth mental health needs to improve preventive strategies and early intervention [2]. Despite the progress achieved over the past two decades, the number of studies conducted in the Arab world is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…detection, prevention and intervention during adolescence can help reduce the burden of mental illness [2][3][4]. To this end, understanding the characteristics, perceived stressors, and pathways to care of youth who develop mental illness is critical to early detection and treatment.…”
mentioning
confidence: 99%
“…Subsequently, the CBPR team refined the Mindful‐Based Self‐Compassion programme (Neff & Germer, 2013) for youth living in a small city centre. The CBPR team also determined that maximum intervention benefit would be for youth undergoing the transition to high school, when mental health symptoms increase (Mei et al., 2020), self‐compassion decreases (Bluth et al., 2017), educational struggles amalgamate (Sutton et al., 2018) and academic disengagement intensifies (Olivier et al., 2020). Furthermore, a school setting was determined to be the desired location for the intervention because rural youth living on peripheries of small city centres struggle to access services outside the school setting (Boydell et al., 2006).…”
Section: Methodsmentioning
confidence: 99%
“…It has been noted that this kind of involvement not only ensures that services are more relevant and appropriate to the population they are seeking to serve, but that it facilitates a youth-friendly and stigma free culture of care [ 54 ] and may be more cost-effective [ 55 ]. There is good evidence that involving young people in the process of service design is a key component to developing effective youth mental health services that address many of the identified barriers to help-seeking for young people [ 8 , 23 , 47 , 56 , 57 , 58 ]. It is particularly notable that some research has suggested that collaboratively designed services have the potential to engage minority young people who are traditionally underserved by conventional mental health services [ 59 ].…”
Section: Introductionmentioning
confidence: 99%